1974
DOI: 10.1111/j.1432-1033.1974.tb03827.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Ovalbumin mRNA in Hen and Chick Oviduct by Hybridization to Complementary DNA

Abstract: 1. DNA complementary to ovalbumin mRNA was synthesized using reverse transcriptase from avian myelobastosis virus and ovalbumin mRNA, purified 60 -70-fold with respect to polysomal RNA, as template.2. The quantitative distribution of ovalbumin mRNA sequences in hen and chick oviduct was determined by hybridization with ovalbumin complementary DNA (cDNA). In hen, we calculate that there are approximately 36000 ovalbumin mRNA molecules per oviduct tubular gland cell.The polysome fraction contains 93 % of ovalbum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
27
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(32 citation statements)
references
References 36 publications
5
27
0
Order By: Relevance
“…During stimulation with estradiol the amount of ovalbumin mRNA dramatically increases from a few copies to tens of thousands of copies per cell (2,4,(5)(6)(7). Similar results have been found for the induction of ovomucoid and lysozyme mRNA (7).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…During stimulation with estradiol the amount of ovalbumin mRNA dramatically increases from a few copies to tens of thousands of copies per cell (2,4,(5)(6)(7). Similar results have been found for the induction of ovomucoid and lysozyme mRNA (7).…”
supporting
confidence: 74%
“…The synthesis of the egg white proteins in the tubular gland cell of the chicken oviduct is primarily related to the cellular accumulation of the corresponding mRNAs (1)(2)(3)(4)(5)(6)(7). During stimulation with estradiol the amount of ovalbumin mRNA dramatically increases from a few copies to tens of thousands of copies per cell (2,4,(5)(6)(7).…”
mentioning
confidence: 99%
“…Our approach involved the translation of nuclear RNA into protein with the wheat-germ cell-free system. Although it is now clear that mRNA originates in the eukaryotic nucleus (Molloy & Puckett, 1976) there are very few reports in the literature of the successful translation of nuclear RNA into protein in vitro (Ruiz-Carrillo et al, 1973;Knochel & Teidemann, 1975), and some workers have found that nuclear RNA inhibits protein synthesis in vitro (Cox et al, 1974). We found that nuclear RNA stimulated protein synthesis in the wheat-germ system at concentrations up to 5,g/50pu1 assay, and ascertained that the observed messenger activity was not due to contamination of the nuclear RNA with cytoplasmic RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of chick intestinal nuclear RNA Nuclei were prepared from chick ileal mucosa by the method described by Cox et al (1974), in order to minimize contamination with ribosomes on the outer nuclear membrane (Knowler et al, 1973), and RNA was isolated from the pellet by a hot phenol/ sodium dodecyl sulphate extraction (Ruiz-Carrillo et al, 1973 It was important for this study to demonstrate that the calcium-binding-protein mRNA designated 'nuclear' did originate from the nucleus and not from contaminating cytoplasmic RNA. In an attempt to obtain a maximum estimate of the extent to which nuclear RNA could be contaminated by cytoplasmic RNA, mucosa from vitamin D-deficient birds (with no calcium-binding-protein mRNA) was homogenized in the post-nuclear supernatant obtained from vitamin D-dosed birds (containing calciumbinding-protein mRNA), and the contamination of nuclei from the deficient birds with trapped cytoplasmic calcium-binding-protein mRNA from the dosed birds was determined by extracting and translating the nuclear RNA in the wheat-germ cell-free system.…”
Section: Nmentioning
confidence: 99%
“…At the end of a 60-min incubation at 25°C, RNA was extracted by the phenol/chloroform method (11) in the presence of wheat germ high molecular weight RNA as carrier (150-fold excess over endogenous nuclear RNA). After 10 min of heat denaturation at 75°C, the Hg-RNA was isolated by SH-agarose column chromatography as described (11,12) 24 hr at 38,000 rpm in a Spinco SW 41 rotor, and an aliquot of each gradient fraction was assayed for radioactivity. X, Position of the 3H-labeled viral marker DNAs centrifuged on a parallel gradient.…”
mentioning
confidence: 99%